Organized labor in partnership with government and management in national development - Ramirez, Rolando C. 4 0 16; 5
u
Thesis (Ph.D.) -- Pamantasan ng Lungsod ng Maynila, 2000.;A dissertation presented to the faculty of the Graduate School of Management in partial fulfillment of the requirements for the degree Doctor of Business Administration.
Keywords: 2 -- 0; 6; 20; 20; 2